Penugasan Multi Objective pada Industri Konveksi di Kabupaten Lamongan - Mohammad Syaiful Pradana; Siti Alfiatur Rohmaniah (UJMC (Unisda Journal of Mathematics and Computer Science), 2024)
There are various problems that must be faced by convection industry owners in Lamongan district in order to get optimal results in their business. These problems can include production costs, production time, production quality and income from products sold. The aim of this research is to optimize problems through implementing a multi-objective assignment method. The assignment method used in this research is the Weighted-Sum method, where this method changes the multi-objective objective function into one objective function by assigning weights to each objective function on a scalar basis. Based on the results of the implementation of the weighted-sum method, a pair of workers with tasks with optimal total resources was obtained.